Pengaruh Hukum Perlindungan Anak dalam Penanganan Kekerasan Seksual di Sekolah - Nilam Cayo, Putri Sari (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Sexual violence against children in the school environment not only violates children's human rights, but also destroys the sense of security that should be the main foundation in the education process. How does child protection law play a role in handling cases of sexual violence in schools, by reviewing both normative aspects (rules of law) and their implementation in the field. This research uses a normative juridical approach and relies on secondary data, such as laws and regulations, court decisions, and literature reviews. The findings show that although Indonesia has strong regulations, such as Law Number 35 of 2014 and Law Number 12 of 2022, the implementation still faces many challenges. The lack of understanding of the authorities on the issue of child sexual abuse, the unavailability of a safe reporting system in schools, and the culture of society that tends to silence victims are the main obstacles. Therefore, more efforts are needed than just making regulations, namely the involvement of all parties, strengthening the capacity of educational institutions, and establishing a protection system that favors children. With these steps, the law can truly be present as a real protector for children in the school environment.